2021
DOI: 10.2352/issn.2470-1173.2021.1.vda-304
|View full text |Cite
|
Sign up to set email alerts
|

Using Augmented Reality to Enhance Nursing Education

Abstract: Fast track article for IS&T International Symposium on Electronic Imaging 2021: Visualization and Data Analysis proceedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The fur-ther support the notion of AR's usefulness in education, Balien et al successfully demonstrated another augmented reality tool that proved to be valuable for existing education approaches in medical training [16]. Menon et al [37] developed an augmented reality application to improve the training of nursing students that showed a measurable improvement in student outcomes. Time and again augmented reality has proven to be advantageous when integrated into education in terms of novelty, memory retention, and knowledge gained [14] [12] [23] [24] .…”
Section: Feasibility Of Using Ar To Train Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fur-ther support the notion of AR's usefulness in education, Balien et al successfully demonstrated another augmented reality tool that proved to be valuable for existing education approaches in medical training [16]. Menon et al [37] developed an augmented reality application to improve the training of nursing students that showed a measurable improvement in student outcomes. Time and again augmented reality has proven to be advantageous when integrated into education in terms of novelty, memory retention, and knowledge gained [14] [12] [23] [24] .…”
Section: Feasibility Of Using Ar To Train Resuscitationmentioning
confidence: 99%
“…The use of augmented reality headsets typically significantly diminishes some of the aforementioned shortcomings of virtual reality headsets as one is not completely detached from the real world. In addition, hand gestures can be used to navigate the application when using the Hololens, and use the handheld controller while using the Magic Leap One device [37]. Munzer et.…”
Section: Ar Triage Training For Multi-casualty Scenariosmentioning
confidence: 99%